2019
DOI: 10.1016/j.clae.2018.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an enhanced viscosity artificial tear for moderate to severe dry eye disease: A multicenter, double-masked, randomized 30-day study

Abstract: In a randomized, controlled clinical trial, two lubricant artificial tear formulations with enhanced viscosity were compared: an investigational product at the time, containing carboxymethylcellulose 1.0% and glycerin 0.9% (CMC-GLY) with osmoprotectants, and a standard formula containing carboxymethylcellulose 1.0% alone (CMC). Methods: This double-masked study recruited patients with moderate to severe dry eye at 10 US centers. After a 7-day run-in with CMC 0.5% (Refresh Tears) patients were randomized to use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 31 publications
1
31
0
1
Order By: Relevance
“…From baseline within 30 days with use of 0.5% carboxymethylcellulose sodium (CMC)/0.9% Glycerin (GLY) eye drops or 0.5% CMC artificial tears, dry eye signs and symptoms based on Schirmer Test, tear break up time (TBUT), corneal and conjunctival staining and OSDI are confirmed to have a significant improvement [121]. Similar findings were also found in another study which evaluated 1.0% CMC/0.9% GLY and 1.0% CMC eye drops for patients with moderate to severe dry eye [122]. Administration of seawater is thought to be more effective than treatment with carmellose artificial tears in reducing pro-inflammatory molecules, such as IL-1 beta and IL-6, in tears among patients with DED [123].…”
Section: Artificial Tearsupporting
confidence: 53%
“…From baseline within 30 days with use of 0.5% carboxymethylcellulose sodium (CMC)/0.9% Glycerin (GLY) eye drops or 0.5% CMC artificial tears, dry eye signs and symptoms based on Schirmer Test, tear break up time (TBUT), corneal and conjunctival staining and OSDI are confirmed to have a significant improvement [121]. Similar findings were also found in another study which evaluated 1.0% CMC/0.9% GLY and 1.0% CMC eye drops for patients with moderate to severe dry eye [122]. Administration of seawater is thought to be more effective than treatment with carmellose artificial tears in reducing pro-inflammatory molecules, such as IL-1 beta and IL-6, in tears among patients with DED [123].…”
Section: Artificial Tearsupporting
confidence: 53%
“…The drops contain sodium carboxymethylcellulose (CMC) 0.5% as the active ingredient, as well as sodium lactate and various electrolytes, including sodium chloride, potassium chloride, magnesium chloride, and calcium chloride. They can be used to relieve symptoms of dry eye, ie, irritation, burning, and discomfort 22…”
Section: Methodsmentioning
confidence: 99%
“…For example, tear-evaporation rate,15 Schirmer's test,16 phenol red thread,16 tear meniscus height (TMH),17 noninvasive tear breakup time (NITBUT),18 osmolarity,19 and the tear ferning (TF)20,21 test can be used to detect dry eye. Artificial tears can be used to lubricate the tear film and relieve some of the uncomfortable symptoms associated with moderate dry eye 22,23…”
Section: Introductionmentioning
confidence: 99%
“…Artificial tears viscosity, unlike density, is highly dependent on chemical composition and varies considerably between different commercial formulas. Bhojwani et al [32] reported measured values from 1 up to ∼600 Pa•s of dynamic viscosity for common high viscosity and low viscosity artificial tears at temperatures from 25 to 37 • C. Lievens et al [35] and Bhojwani et al [32] presented studies to determine the effect of tears viscosity on well-being in dry eye patients, and reported a slight improvement with the increase of viscosity, while some others reported no improvements at all.…”
Section: Hagen-poiseuille Flowmentioning
confidence: 99%